Dire son parcours de transclasse - Paul Bouffartigue (La Nouvelle Revue du Travail)
Three recent works by sociologists have enriched the corpus of autosociobiographical narratives of “trans-classes” and controversies about them. Here, we investigate the identity of those writing, visible among social migrants in high social ascent, then show the differences between the books of Gilles Moreau and Norbert Alter and the paths they report. We conclude by critiquing Gérald Bronner’s thesis, according to which “dolorism” marks the stories of trans-classes and by questioning the sources of a certain social demand towards this literary and sociological genre.